2009
DOI: 10.4049/jimmunol.0902372
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Cassette Transporter G1 Negatively Regulates Thymocyte and Peripheral Lymphocyte Proliferation

Abstract: Cholesterol is a key component of cell membranes and is essential for cell growth and proliferation. How the accumulation of cellular cholesterol affects lymphocyte development and function is not well understood. We demonstrate that ATP-binding cassette transporter G1 (ABCG1) regulates cholesterol homeostasis in thymocytes and peripheral CD4 T cells. Our work is the first to describe a cell type in Abcg1-deficient mice with such a robust change in cholesterol content and the expression of cholesterol metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 54 publications
14
111
0
Order By: Relevance
“…Independent groups have indeed reported proliferative advantages in ABCG1 null lymphocytes (20,49) and in human prostate cancer cells with knockdown expression of ABCA1 (50). In our studies, macrophages with deficient expression of ABCA1 or ABCG1 did show higher proliferation levels compared with control cells, which supports the idea that increased availability of intracellular cholesterol favors proliferative responses.…”
Section: Discussionsupporting
confidence: 87%
“…Independent groups have indeed reported proliferative advantages in ABCG1 null lymphocytes (20,49) and in human prostate cancer cells with knockdown expression of ABCA1 (50). In our studies, macrophages with deficient expression of ABCA1 or ABCG1 did show higher proliferation levels compared with control cells, which supports the idea that increased availability of intracellular cholesterol favors proliferative responses.…”
Section: Discussionsupporting
confidence: 87%
“…ABCG1 is highly expressed in various immune cells including macrophages and T lymphocytes. Bensinger et al illustrated an important role for ABCG1 in T cell proliferation (13), and our group also reported that ABCG1-deficient CD4 + T cells showed enhanced T cell receptor signaling due to altered lipid raft formation (14). The development and function of NKT cells is also affected by the absence of ABCG1 in a cell-intrinsic manner (15).…”
Section: Introductionmentioning
confidence: 53%
“…Western blotting and quantitative RT-PCR (qRT-PCR) analysis were performed essentially as previously described (15,72). For Western blotting, RIPA buffer (50 mM TrisHCl, pH 8.0, 150 mM NaCl, 1% Igepal, 10 mM NaF, 2 mM Na3VO4, and Sigma-Aldrich proteases inhibitor cocktail) was added to cells to generate whole-cell lysates.…”
Section: Methodsmentioning
confidence: 99%